At the edge: An exploration of the boundary condition between architecture and nature - Botha, Vivian May (School of Architecture, Planning and Geomatics, 2017)
An interest in abandoned and derelict landscapes as environmentally appropriate spaces for architectural interventions led my dissertation research to the theoretical concept of terrain vague. The terrain vague sites found within the City of Cape Town revealed that it is the edge condition which differentiates these spaces as being outside the realm of the normative city. The unravelling of the edge from a state of order to disorder took my research to the historical fortifications of Table Bay and specifically, the Settlement's eastern boundary demarcated by the French Lines. A combination of redoubts and connecting rampant walls which marked the boundary between the order of the European settlement and the wilderness beyond. The Central Redoubt is the only remnant of these structures and is located on Trafalgar Park in the suburb of Woodstock. Trafalgar Park is surrounded and fragmented by a variety of boundary conditions and controlled access which results in the Park being severely underutilised. The dissertation design project looks at re-activating Trafalgar Park through the manipulation of its various edge conditions. The transformation of boundaries into pedestrian routes and public space around points of interest aims to improve accessibility and encourage connections between the Park and surrounding context. The Swimming Pool Precinct was chosen as the site for the architectural intervention as it is an impacted site that offers the opportunity to increase activity and improve the connection between the north and south of the Park. The interrogation of the boundary condition between architecture and nature through the design of edges and thresholds is the driving concept behind the architectural design. The dissertation design project aims to demonstrate that appropriate architectural interventions are able to increase activity in public areas within the City of Cape Town without the need for fences and controlled access.